PERAN SUMBER SUMBER PELATIHAN DAN PENGEMBANGAN DALAM MENINGKATKAN KINERJA - Purba, Frans Tamba Raja; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
Human resources (HR) training and development play a pivotal role in enhancing organizational effectiveness and employee performance. This study explores the significance of HR training and development in improving employee performance through a comprehensive systematic literature review (SLR). Relevant literature was gathered from various academic databases, including Google Scholar, Scopus, and Mendeley, to ensure a diverse and comprehensive collection of studies. The findings indicate that HR training and development programs positively influence employee skills, competence, and productivity, leading to improved performance. This research emphasizes the importance of aligning training and development initiatives with both individual employee needs and broader organizational strategies. The results suggest that organizations investing in HR training and development can achieve long-term success by fostering a skilled and motivated workforce.